Martin Luther : a biography for the people - Daughrity, Dyron B., 1973- (Abilene Christian University Press, 2017)
"Martin Luther is a fresh retelling of one the most significant figures of the last millennium. Not written primarily for theologians, but rather for a general audience, Martin Luther traces Luther's early development, his conflicts with civic and religious authorities, his leadership of reform in Germany, and the subsequent impact of Luther's writings and beliefs as they stretched around the world."--Publisher